Rian Fahardhi as a Generation Z Role Model: An Analysis of Inspirational Content on Instagram @rian.fahardhi - Siska; Hadisaputra; Nelly Saputri; Hajaratul Aswad; Isda Lestari (Aksiologi : Jurnal Pendidikan dan Ilmu Sosial, 2025)
Social media has become a primary tool for Generation Z to express themselves and find inspiration. This study explores Rian Fahardhi's role as a role model for Generation Z through content analysis of his Instagram posts, @rian.fahardhi. Using qualitative methods and a content analysis approach, this study examines six Instagram posts selected based on the themes of inspiration, motivation, and behavioral guidance. The results show that Rian Fahardhi's content consistently conveys positive messages, such as the spirit of never giving up, creativity, and courage. Through visual and narrative elements, Rian successfully influences his audience's mindset, encouraging them to set and achieve life goals and internalize positive values. Based on George Gerbner's Cultivation theory, repeated exposure to these messages can shape Generation Z's perceptions of social reality and behavioral norms. This study highlights the importance of social media as a platform for building positive perceptions and the influence of public figures in shaping the identity and social values ​​of the younger generation. This study contributes to the development of literature on the role of social media in shaping Generation Z's behavior. Keywords: Rian Fahardhi, Generation Z, Role Model, Instagram